2023
DOI: 10.1051/0004-6361/202347239
|View full text |Cite
|
Sign up to set email alerts
|

The compactness of ultra-faint dwarf galaxies: A new challenge?

Yves Revaz

Abstract: So far, numerical simulations of ultra-faint dwarf galaxies (UFDs) have failed to properly reproduce the observed size–luminosity relation. In particular, no hydrodynamical simulation run has managed to form UFDs with a half-light radius as small as 30 pc, as seen in observations of several UFD candidates. We tackle this problem by developing a simple but numerically clean and powerful method in which predictions of the stellar content of UFDs from ΛCDM cosmological hydrodynamical simulations are combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Despite the overlap of simulations with the brighter UFDs, most simulations are unable to produce analogs of the most compact observed UFDs (r h ∼ 30 pc; e.g., Revaz 2023). Rather, they are creating UFDs with half-light radii up to an order of magnitude larger than observed.…”
Section: Do Simulated Ufds Match Observations?mentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the overlap of simulations with the brighter UFDs, most simulations are unable to produce analogs of the most compact observed UFDs (r h ∼ 30 pc; e.g., Revaz 2023). Rather, they are creating UFDs with half-light radii up to an order of magnitude larger than observed.…”
Section: Do Simulated Ufds Match Observations?mentioning
confidence: 97%
“…Rather, they are creating UFDs with half-light radii up to an order of magnitude larger than observed. Revaz (2023) speculates that this could be due to resolution limits, spurious numerical heating, or improper feedback prescriptions, although the widespread nature of the pattern suggests there is no singular factor. In their own work using DM-only simulations, Revaz (2023) found that minihalo mergers played a large role in the expansion of the simulated UFD sizes.…”
Section: Do Simulated Ufds Match Observations?mentioning
confidence: 99%